An Unexpected Case of Black Mamba (Dendroaspis polylepis) Bite in Switzerland - Verena Quarch; Lukas Brander; Luca Cioccari (Case Reports in Critical Care)
Mambas (genus Dendroaspis) are among the most feared venomous African snakes. Without medical treatment, mamba bites are frequently fatal. First-aid treatment includes lymphatic retardation with the pressure immobilization technique. Medical management comprises continuous monitoring, securing patency of the airway, ensuring adequate ventilation, symptomatic measures, and administration of specific antivenin. We report an unusual case of a snake breeder bitten by a black mamba in Switzerland, report the clinical course, and review the lifesaving emergency management of mamba bites. This case highlights the importance of early antivenin administration and suggests that emergency and critical care physicians as well as first responders all around the world should be familiar with clinical toxinology of exotic snake bites as well as with the logistics to most rapidly make the specific antivenin available.